Flower gnomigurumi : 12 cute amigurumi gnomes to crochet - Iglesias Silva, Madelenón-Soledad (Dover Publications, 2024)
"Create an amigurumi world of whimsical, fun-loving, cute gnomes adorned with nature's loveliest blossoms. This enchanting book offers twelve distinct gnome patterns, each embellished with beautiful blooms ranging from asters, carnations, chrysanthemums, and daffodils to daisies, lilies, marigolds, roses, and other floral beauties. You don't have to be an expert to crochet these adorable gnomes - the patterns are suitable for crocheters of all skill levels. Easy-to-follow, step-by-step instructions are accompanied by full-color photographs, serving as a visual aid for your gnome-making adventure. Materials and tools necessary for each gnome are explicitly highlighted, making your crafting journey as smooth as possible. Gift these charming handmade flower gnomes to friends, family, and garden lovers, or keep them as part of your own treasured collection"--